Mid to late Holocene strengthening of the East Greenland Current linked to warm subsurface Atlantic water. (1st December 2015) - Perner, Kerstin; Moros, Matthias; Lloyd, Jeremy M.; Jansen, Eystein; Stein, Rüdiger
Abstract: The relatively fresh and cold East Greenland Current (EGC) connects the Arctic with the subpolar North Atlantic Ocean. Its strength and influence on the freshwater balance in the North Atlantic affects both the Subpolar Gyre dynamics and deep convection in the Labrador Sea. Enhanced freshwater and sea-ice expansion in the subpolar North Atlantic is suggested to modify the northward heat transport within the North Atlantic Current. High-resolution palaeoceanographic reconstructions, based on planktic and benthic foraminifera assemblage data, from the central East Greenland shelf (Foster Bugt) reveal distinct centennial to millennial-scale oceanographic variability that relates to climatic changes during the mid to late Holocene (the last c. 6.3 ka BP). Our data highlight intervals of cooling and freshening of the polar surface EGC waters that accompany warming in the subsurface Atlantic waters, which are a combination of chilled Atlantic Intermediate Water (AIW) from the Arctic Ocean and of the Return Atlantic Current (RAC) from the West Spitsbergen Current (WSC). Mid Holocene thermal optimum conditions prevailed until c. 4.5 ka BP. A thin/absent surface Polar Water layer, low drift/sea-ice occurrence and strong contribution of recirculating warm Atlantic waters at the subsurface, suggest a relatively weak EGC during this period. Subsequently, between 1.4 and 4.5 ka BP, the water column became well stratified as the surface Polar Water layer thickened and cooled, indicating a strong EGC. This EGC strengthening parallelled enhanced subsurface chilled AIW contribution from the Arctic Ocean after c. 4.5 ka BP, which culminated from 1.4 to 2.3 ka BP. This coincides with warming identified in earlier work of the North Atlantic Current, the Irminger Current, and the West Greenland Current. We link the enhanced contribution of chilled Atlantic Water during this period to the time of the 'Roman Warm Period'. The observed warming offshore East Greenland, centred at c. 1.8 ka BP, likely occurred in response to changes in the interactions of i) a weakened Subpolar Gyre; ii) increased northward heat advection in the North Atlantic Current, and iii) a predominant positive North Atlantic and Arctic Oscillation mode, prevailing during the time of the Roman Warm Period. Highlights: High-resolution planktic/benthic foraminiferal record from the core of the EGC. From 4.5 ka BP strengthening/expansion of the EGC flow. Parallelled by enhanced contribution AIW from the Arctic Ocean. Maximum AIW flow, centred at 2.0 ka BP, suggests subsurface warming. Subsurface warming occurs simultaneous to distinct warming in the North Atlantic.